Turkey's new cabinet: A wind of change in Turkish politics? - Hürcan Aslı Aksoy; Yaşar Aydın; Salim Çevik (Stiftung Wissenschaft und Politik (SWP), 2023)
The inclusion of technocrats and bureaucrats in Turkey's new cabinet has led to cautious optimism over a possible change in direction. While President Recep Tayyip Erdoğan's choice of economy minister hints at a reset, the thrust of foreign policy will remain unchanged. Here Ankara will pursue a moderate and diplomatic approach while still pursuing strategic autonomy. A great deal will depend on what Erdoğan wants and how he chooses to employ foreign relations to attract better financial and economic deals. Given Turkey's importance as a security partner, especially in light of Russia's war against Ukraine, the EU needs to develop a strategic approach on the basis of common interests and institutionalised relations.
Keywords: 320; Turkey; EU-Turkey relations; President Recep Tayyip Erdoğan; People's Alliance; Justice and Development Party (AKP); Nationalist Movement's Party (MHP); Republican People's Party (CHP); Kemal Kılıçdaroğlu; Mehmet Şimşek; Hakan Fidan; Suleyman Soylu; Hulusi Akar